Active chlorophyll fluorescence technologies in precision weed management: overview and perspectives - Hu, Jin; Xie, Yuwen; Ban, Xingyu; Zhang, Liyuan; Zhou, Zhenjiang; Zhang, Zhao; Wang, Aichen; Waine, Toby W. (MDPI, 2025)
Weeds are among the primary factors that adversely affect crop yields. Chlorophyll fluorescence, as a sensitive indicator of photosynthetic activity in green plants, provides direct insight into photosynthetic efficiency and the functional status of the photosynthetic apparatus. This makes it a valuable tool for assessing plant health and stress responses. Active chlorophyll fluorescence technology uses an external light source to excite plant leaves, enabling the rapid acquisition of fluorescence signals for real-time monitoring of vegetation in the field. This technology shows great potential for weed detection, as it allows for accurate discrimination between crops and weeds. Furthermore, since weed-induced stress affects the photosynthetic process of plants, resulting in changes in fluorescence characteristics, chlorophyll fluorescence can also be used to detect herbicide resistance in weeds. This paper reviews the progress in using active chlorophyll fluorescence sensor technology for weed detection. It specifically outlines the principles and structure of active fluorescence sensors and their applications at different stages of field operations, including rapid classification of soil and weeds during the seedling stage, identification of in-row weeds during cultivation, and assessment of herbicide efficacy after application. By monitoring changes in fluorescence parameters, herbicide-resistant weeds can be detected early, providing a scientific basis for precision herbicide application.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3002 Agriculture, land and farm management; 3004 Crop and pasture production; chlorophyll fluorescence (ChlF); weed detection; site-specific weed management (SSWM); herbicide resistance; active ChlF sensor; precision agriculture